IMPLEMENTING CLASSROOM MANAGEMENT FOR YOUNG CHILDREN AT PAUD BUNGONG JEUMPA, ACEH BESAR - Ayu Hanidar; Hazal Fitri; Safriadi; Maidar (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to describe the implementation of classroom management for young children at PAUD Bungong Jeumpa, Aceh Besar, to identify the factors that support its implementation, and to analyses the constraints encountered. A descriptive qualitative approach was adopted, with data gathered through observation, semi-structured interviews, and documentation. The research participants comprised the school principal, who served as the principal informant, and one teacher, who served as a supporting informant. Data were analyzed using the interactive model of Miles and Huberman, comprising data reduction, data display, and conclusion drawing, while trustworthiness was established through source, method, and time triangulation. The findings indicate that classroom management at PAUD Bungong Jeumpa has been implemented reasonably well across the planning, implementation, and evaluation stages. Teachers foster a safe, comfortable, and enjoyable learning environment consistent with the developmental characteristics of young children by adopting play-based learning approaches, arranging the physical environment flexibly, and applying positive behavioral guidance. The principal supporting factors identified were collaboration among the principal, teachers, and parents; the availability of facilities and infrastructure; teacher competence; and a conducive school environment. The constraints identified were variation in children's individual characteristics, limited facilities and learning media, restricted instructional time, and inconsistent communication with some parents. These findings extend the existing evidence base on early childhood classroom management by illustrating how a rural, faith-based early childhood Centre in Aceh negotiates resource constraints through relational, play-based strategies. Continuous strengthening of classroom management—through teacher professional development, improved facilities, and closer home–school communication—is essential for improving the quality of early childhood education.